Density‐Dependent Metabolic Costs of Copper Exposure in a Coastal Copepod. (29th July 2021) - Lode, Torben; Heuschele, Jan; Andersen, Tom; Titelman, Josefin; Hylland, Ketil; Borgå, Katrine
Abstract: Traditional ecotoxicology methods involving copepods have focused on exposure of pooled individuals and averaged responses, but there is increasing awareness of the importance of individual variation. Many biological traits are density dependent, and decisions to use single‐individual or pooled exposure may affect responses to anthropogenic stressors. We investigated how conspecific density as a biotic stressor affects behavioral and respiratory responses to copper (Cu) exposure in the coastal copepod Tigriopus brevicornis . Adults were incubated at densities of 1, 2, or 4 individuals per replicate in 3.2 mL of exposure medium (23 µg Cu L –1 or control). Our results show an interaction of Cu exposure and density on respiration. The Cu exposure increased respiration, but this effect diminished with increasing density. We also found reduced swimming activity with increasing density. We propose 2 nonexclusive alternative explanations for the density‐dependent respiratory increase of Cu exposure: 1) a behavioral stress response to low conspecific density, or 2) increased Cu exposure due to increased swimming activity. We emphasize the importance of considering density‐dependency in responses when designing and interpreting ecotoxicology studies. Environ Toxicol Chem 2021;40:2538–2546. © 2021 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.